Biological role of Nardonella endosymbiont in its weevil host. - Takashi Kuriwada; Takahiro Hosokawa; Norikuni Kumano; Keiko Shiromoto; Dai Haraguchi; Takema Fukatsu (PLoS ONE, 2010)
Weevils constitute the most species-rich animal group with over 60,000 described species, many of which possess specialized symbiotic organs and harbor bacterial endosymbionts. Among the diverse microbial associates of weevils, Nardonella spp. represent the most ancient and widespread endosymbiont lineage, having co-speciated with the host weevils for over 125 million years. Thus far, however, no empirical work on the role of Nardonella for weevil biology has been reported. Here we investigated the biological role of the Nardonella endosymbiont for the West Indian sweet potato weevil, Euscepes postfasciatus. This insect is an experimentally tractable pest insect that can easily be reared on a natural diet of sweet potato root as well as on an agar-based artificial diet. By larval feeding on an antibiotic-containing artificial diet, Nardonella infection was effectively eliminated from the treated insects. The antibiotic-treated insects exhibited significantly lighter body weight and lower growth rate than the control insects. Then, the antibiotic-treated insects and the control insects were respectively allowed to mate and oviposit on fresh sweet potatoes without the antibiotic. The offspring of the antibiotic-treated insects, which were all Nardonella-negative, exhibited significantly lighter body weight, smaller body size, lower growth rate and paler body color in comparison with the offspring of the control insects, which were all Nardonella-positive. In conclusion, the Nardonella endosymbiont is involved in normal growth and development of the host weevil. The biological role of the endosymbiont probably underlies the long-lasting host-symbiont co-speciation in the evolutionary course of weevils.